2014
DOI: 10.1002/cplu.201402077
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Silver and Fluorescent Dyes Incorporated in Self‐Assembling Peptides and Their Potential Applications in Biology

Abstract: There is increasing interest in studying the interaction of nanoparticles with biomolecules, microorganisms, and noble metals to explore their unique properties and potential biological applications. The synthetic butyloxycarbonyl (Boc)‐protected methyl esters of peptides composed of only aliphatic amino acids (Boc‐Ile‐Ile‐OMe and Boc‐Leu‐Ile‐Ile‐OMe) self‐assembled into nanotubes and spheres, respectively, has been previously demonstrated. Herein, the characterization of these peptide nanoparticles incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Rigid crystalline structure of fully protected dileucine is rare . Therefore, to understand their self‐assembly in molecular level, we investigated the structure of P1 and P6 in both solid and solution states.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rigid crystalline structure of fully protected dileucine is rare . Therefore, to understand their self‐assembly in molecular level, we investigated the structure of P1 and P6 in both solid and solution states.…”
Section: Resultsmentioning
confidence: 99%
“…Although, H-Leu-Leu-OH crystallized in presence [37] /absences [13] of dimethylsulfoxide (DMSO) and also as trifluoroacetate cocrystal, [38,39] similar rigid self-assembly for C-/N-termini substituted analogues is scarce. [2,3] In one of our previous studies, [40] tertbutyloxycabonyl (Boc) protected dileucine having a propargyl group at C-terminus (Boc-Leu-Leu-Propyne, P1 in Figure 1) self-assembled to construct hollow micro-tubes ( Figure 2). Powder X-ray diffraction (PXRD) study of P1 indicated its crystalline nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Silver nanoparticles could be trapped in the nanostructures formed by the dipeptide. [22] In an effort to examine whether dipeptides composed of hydrophobic amino acids Val, Leu and their combinations can also form nanostructures, we have investigated the self-assembly of four dipeptides 1-4 composed of varying combinations of Val, Leu and Ile. The solvents for dissolution were MeOH as well as the structure-promoting solvent TFE [23] and HFIP.…”
Section: R Esu L Tsmentioning
confidence: 99%
“… 14 , 15 Target delivery of AP is necessary due to their short half-life and relative toxicity against healthy cells. 16 The effective use of nanoscale proteins and peptides in therapeutic and diagnostic methods is a strategy to induce and maintain their functional conformation.…”
Section: Introductionmentioning
confidence: 99%